ALIH KODE DAN CAMPUR KODE INTERAKSI GURU DAN SISWA DI SMK NEGERI 1 PALU - Syamsuddin Syamsuddin (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
This research is titled: ‘’Code Switching and Code Mixing Teacher and Students Interaction at SMK Negeri 1 Palu’’. The objectives of this study are (1) to describe the form of code switching and code mixing in teacher and student interactions at SMK Negeri 1 Palu, (2) to know function of code switching and code mixing, (3) to describe the factors that influence code switching and code mixing in teacher and student interactions during the learning process teach in the class. This research was conducted at SMK Negeri 1 Palu with the research subject being an English teacher. The research is focused on the phenomenon of code switching and code mixing in the interaction of teachers with students during teaching and learning in the classroom and the factors that influence them. The results of the study show that: (1) the form of teacher code switching consists of two parts, namely the language used in communication consists of formal and informal. In addition, the relationship between languages is in the form of code switching form English-Indonesian and Indonesian-English, (2) the functions code switching and code mixing in interaction teacher with students, (3) The factors that influence code switching and code mixing are the realitonship between the speaker and the speech partner, the change in the situasion from formal to informal or vice versa, and changes in the topic of conversation